Identification of Water Quality Status In the Upstream of the Siak River, Kampar, using a Storet Method - Arief, Rahmat; Sumiarsih, Eni; El Fajri, Nur (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRAKIn the upstream of the Siak River, there are various activities, such as palm plantations, palm oil industry, fishcapture andwater transportation that produce pollutant and thus affect the water quality. A research aims to determine the quality and quality status of the upstream waters of the Siak River, a study was conducted from April-May 2017. The water was sampled at 3 stations, with 3 replications. Water quality parameters measured were temperature, pH, current speed, dissolved oxygen, depth, and brightness (in the field), BOD5, COD, TSS, Nitrate, Phosphate, Oil and Fat (in laboratory). Results shown thatthe BOD5 is 16.7 - 38.9 mg/L and oil and fat content was 86,000-339,000 mg/L, these values are higher that that of the standard issued by the Indonesian government. The water temperature ranges from 30-31oC, pH5, current speed 0.3-0.4cm/s, dissolved oxygen 3.1-4.4 mg/L, depth 4-5 m, brightness 35-61cm, COD 8.5-17.6 mg/ L, nitrate 0.56-1.29 mg/L and phosphate 0.24-0.28 mg/L.based on data obtained, it can be concluded that upstream of the Siak River is classified as moderately polluted (score ranged from -20 to - 22). Key words: polluted river,palm oil industry, oil dan fat